INTERNALISASI MODERASI BERAGAMA DALAM PENGEMBANGAN KURIKULUM MERDEKA DI SMPN 8 SATAP TELAGA BIRU - mohamad, sandra; Yahiji, Kasim; Yasin, Zohra; Arsyad, Lukman (Inspiratif Pendidikan, 2023)
Abstract: This study explains the Internalization of Religious Moderation in the Development of the Independent Learning Curriculum at SMPN 8 Satap Telaga Biru. This type of research used is qualitative research using formal and material research objects. Any data collection technique looks for data that will be used to find out a picture of what will be researched, discussed or analyzed. And the data processing techniques used process data into information The results of this study show that based on the discussion, researchers concluded that the implementation of religious moderation must be applied in the educational environment in the formation of moderate attitudes in religion for students. For this reason, it is necessary to develop a PAI curriculum in schools that teach Islamic moderation, pesantren education to present a moderate Islamic movement among students who develop teachings: (1) to build harmony (tolerance) among different groups, both outside Islam and within Islam itself; (2) spreading peace in their social environment; (3) promoting interfaith dialogue and (4) instilling openness with outsiders and 4) rejecting hate speech (hoaxes) both inside and outside the school.